A POST OPERATIVE PALATOPLASTY FEEDING GUIDELINES: A LITERATURE REVIEW - Salim, Darryl Samuel; Victe, Dona Christin; Sylvina, Sylvina; Setyarto, Muhammad Rizqy (Lingkar Studi Bedah Plastik Foundation, 2023)
Introduction: Post operative palatoplasty is one of the important things, because many complications that may occur post operatively such as bleeding, dehiscence, to velopharyngeal insufficiency. One of the factors that determine postoperative palatoplasty wound healing is feeding problem which is still controversial, both in terms of the type of food and the time of feeding. There are no guidelines for handling postoperative palatoplasty in Indonesia. For this reason, the author tries to make a feeding guides post palatoplasty by compiling existing literature, to be used as a reference in making guidelines. Method: Data collected from journal search engine with limited keyword. All article were analysed by authors to find focused data post palatoplasty feeding. All data is presented in a table, then compared and analysed. Result: There are nine articles that met the inclusion and exclusion criteria were obtained which were presented in the table and compared. Conclusion: Guidelines for post palatoplasty surgery must be made to provide the best results. Based on existing research and literature, the authors suggest including: a liquid diet after surgery, a soft diet as soon as possible, a solid diet after one month of surgery, and most importantly all diets must have good nutrition for Indonesia post palatoplasty feeding guidelines.